ChemInform Abstract: Syntheses of Nucleosides with 2′‐Spirolactam and 2′‐Spiropyrrolidine Moieties as Potential Inhibitors of Hepatitis C Virus NS5B Polymerase. Issue 50 (16th December 2014) - Dang, Qun; Zhang, Zhibo; Tang, Bingyu; Song, Yang; Wu, Ling; Chen, Tongqian; Bogen, Stephane; Girijavallabhan, Vinay; Olsen, David B.; Meinke, Peter T.
Abstract The synthesis of nucleosides with 2‐spirolactam (III) and 2‐spiropyrrolidine (IV) moiety is based on the key intermediate (II) which is obtained through epoxide ring opening.